2008
DOI: 10.1159/000141652
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Computed Tomography Evaluation of Peripheral Airways in Asthma Patients: Comparison of Focal and Diffuse Air Trapping

Abstract: Background: Air trapping evaluated in high-resolution computed tomography (HRCT) reflects changes in small bronchi. We simultaneously evaluated focal and diffuse air trapping in asthmatic patients. Objectives: (1) To evaluate air trapping and bronchial wall thickness in asthmatics. (2) To estimate the relationship between air trapping and bronchial wall thickness, pulmonary function tests (PFTs), age, gender and asthma severity. (3) To compare air trapping between subgroups of asthmatic patients with normal FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 70 publications
0
12
0
1
Order By: Relevance
“…Nevertheless, low-density areas are not specific for air trapping since emphysema and local hypoperfusion of lung tissue may have the same effect. Various methods have been reported for air-trapping measurement using CT, from visual grading [41] to manual counting [42]. A Semiautomatic method of quantification has been reported using the density mask technique.…”
Section: Quantitative Ct Of Small Airwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, low-density areas are not specific for air trapping since emphysema and local hypoperfusion of lung tissue may have the same effect. Various methods have been reported for air-trapping measurement using CT, from visual grading [41] to manual counting [42]. A Semiautomatic method of quantification has been reported using the density mask technique.…”
Section: Quantitative Ct Of Small Airwaymentioning
confidence: 99%
“…In asthmatic patients, air-trapping scores correlated with small airway obstruction, assessed by FEV1 and FEF25–75%, which is consistent with small distal airway alterations. Moreover, the focal and diffuse air trapping (E/I ratio) have been shown to correlate with airway wall thickness (WA%) [42]. This should indicate that the remodelling process involves both proximal and distal airways in asthma.…”
Section: Quantitative Ct Of Small Airwaymentioning
confidence: 99%
“…In asthma, Mikos et al [24] measured air trapping on CT scans thanks to a manual method, at a window level of −600 HU and a window width of 1600 HU. Focal air trapping was assessed on end-expiratory scans, superimposing a 10 × 10 mm grid.…”
Section: Quantitative Measurement Of Airways and Lung Parenchyma Umentioning
confidence: 99%
“…Mikos et al using a manual method, showed that focal and diffuse air trapping (E/I ratio) correlated with airway wall thickness (WA%) [24]. Focal air trapping was significantly increased in a subgroup of 10 asthmatics patients with normal FEV1% predicted and FEV1/FVC%.…”
Section: Quantitative Ct In Asthmamentioning
confidence: 99%
“…С помощью КТВР показано, что у больных БА с нормальными значениями показате лей функции внешнего дыхания (ФВД) имеет место неоднородность вентиляции и наличие локальных "воздушных ловушек", что может указывать на не достаточный контроль над воспалением в мелких бронхах при нормальном ОФВ1 [32][33][34].…”
Section: пульмонология 2'2011unclassified